Aplikasi Informasi Promo Pusat Perbelanjaan di Surabaya - Gladys Clarisa Tamyn; Yulia Yulia; Justinus Andjarwirawan (Jurnal Infra, 2018)
Promotions is a frequent offer of various outlets to attract buyers. Promotions information is then much sought after by the community because it can provide benefits when buying goods at the time of promo. To find the desired promotions information must be through social media, website or print media. In order to facilitate the search for promo information required applications that can support the needs of promotions search by the community. Steps to do is find the promo data. The data taken is a promotions held some selected outlets in Galaxy Mall Surabaya as data to be used for promo applications.Applications created in scientific papers can facilitate the searching of promotions information by doing a promotions search based on the desired grouping. The downside of this promo app is that it has not been able to provide notifications and data owned focused on a single shopping center.